Solvability criterion of linear boundary-value problems for integro-differential Fredholm equations with a degenerate kernel in Banach spaces - Boichuk , A. A.; Zhuravlev , V. F. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.983 Using the theory of generalized inversion of operators and integral operators, we obtain a criterion for solvability and a general form of solutions of linear boundary-value problem for integro-differential equation with a degenerate kernel in Banach space.